(untitled) (International Journal of Current Engineering and Technology, 2014)
During the last decade the decrease in the size of computing machinery, coupled with the increase in their computing power has led to the development of the concept of mobile computing. Mobile Computing is a generic term is evolved in modern usage such that it requires that the mobile computing activity be connected wirelessly to and through the internet or to and through a private network. Now a days Mobile internet has changed the way we work and we live, one can easily reached people around the globe instantly, from any device, over any network. The adoption of Internet services has shown to be more difficult due to the difference between the Internet and the mobile telecommunication system. Security is the key issue that needs to be considered, which comes into picture once. The communication channel is set up. This paper provides an insight on threats, challenges and recent trends security issues in mobile computing.